The Effect of Biocard Learning Media on Students' Understanding of Concepts Related to the Human Reproductive System in the 11th Grade Science Class at SMA Diponegoro Panti Jember during the Academic Year 2022/2023 - Kamil, Ahmad Humaidi; Nurlim, Risma; Nurlim, Idiawati (META: Journal of Science and Technological Education, 2023)
The purpose of this study is to determine the effect of using Biocard Media on students' competence in comprehending the material regarding to the Human Reproductive System. The research used a quantitative technique utilizing a Quasi experimental research design known as Nonquivalent Group Posttest Only Design. The sampling technique utilized a purposive sampling technique, with science class 2 being chosen as the control group and science class 1 as the experimental group. Data gathering methods include assessments and written documentation. The data analysis approach utilizes the t test. The research findings indicate that the experimental class students achieved a higher average score for mastery of concepts in the posttest compared to the control class. Specifically, the average score was 75.77 for the experimental class and 70.96 for the control class. Additionally, it was shown that Biocard Media had a substantial impact on students comprehension of concepts, as indicated by a significance value of 0.026.